Schrödinger’s American: A Self-Reflection of One Person’s Role in Iceland’s Nordic and Arctic Discourse - Jonathan Wood (Nordicum-Mediterraneum, 2021)
Introspection and personal story-telling has often been used outside of academia in order to foster dialogue between cultures and peoples. However, this device is rarely used within academia in order to foster debate about cultures, regions, and locales. Through my own personal story, the article brings up questions of belonging within a region that has increasingly come under the microscope. The Arctic has many such stakeholders whose status remains unsolidified or questioned. While my story does not have such questions of legal status, it reflects the insecurity that many feel within a region that has only recently become the focus of colonial hegemony and internationally organized governance. While my positions myself within the region, it is the goal that this paper may inspire others to do the same in order to find common ground upon which we can help connect one another in a region so physically dispersed yet culturally connected.